Diamond@carbon-onion hybrid nanostructure as a highly promising electrocatalyst for the oxygen reduction reaction. Issue 33 (15th March 2016) - Koh, Jaekang; Park, Sung Hyeon; Chung, Min Wook; Lee, Seung Yong; Woo, Seong Ihl
Abstract : The sp 3 -hybridized diamond structure was deliberately preserved at the core to retain stability, while modifying the sp 2 -hybridized surface carbon layers to enhance the ORR activity. Abstract : The modification of nanodiamond derived carbon nano-onions by the formation of additional edge- and defect-sites through the rupturing of surface graphene layers is investigated for its application towards the oxygen reduction reaction (ORR) in acidic media. The catalyst, which had a high degree of edge- and defect-sites on its surface, demonstrated a remarkably enhanced ORR performance compared to that of an edge- and defect-sites poor catalyst, where the onset potential increased from 0.53 to 0.91 V, with a mass activity of 2.70 mA mg −1 (at 0.8 V). According to our electrochemical impedance spectroscopy study, the enhancement in the catalytic performance between the two catalysts could have originated from the charge transfer resistance. Moreover, an accelerated degradation test revealed the outstanding stability of the edge- and defect-rich catalyst, compared to that of Pt/C performed in harsh conditions, which could have originated from the diamond core. The selection of carbon material with adequate modifications to enhance the catalytic activity and stability towards the ORR drafted a scheme for potential catalysts.